2010
DOI: 10.1002/pmj.20181
|View full text |Cite
|
Sign up to set email alerts
|

Opening the “Black Box” of Collective Competence in Extreme Projects: Lessons from the French Special Forces

Abstract: Developing teams capable of completing projects in extreme situations is becoming a major challenge for a growing number of organizations. The notion of collective competence is increasingly being seen as a vital precondition for the success of project teams, particularly in extreme environments. However, we still know little about the ingredients of this collective competence. To partially fill this gap, we make use of the insights offered by the very particular world of the French Special Forces, which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
19
0
6
Order By: Relevance
“…From a case study of one complex public-private partnership, Ruuska and Teigland (2009) highlighted four ingredients to ensure project success through collective competence: (1) co-developing a clear project charter; (2) recruiting a project leader with strong knowledge broker skills; (3) conducting joint problem-solving tasks using boundary objects; and (4) ensuring an understanding of the "big picture" through continuous open and balanced communication. For their part, Melkonian and Picq (2010) made use of the insights offered by the very particular world of the French Special Forces, which have been operating successfully for several decades in extreme environments. Based on an in-depth qualitative study of their project-based mode of operations, they detail the six main ingredients of the collective competence that underpins the activities of commando units in mission: (1) the high individual expertise; (2) the combination of different but complementary forms of expertise; (3) the construction of a shared representation, based on common frames of reference and languages; (4) the capacity for collective improvization; (5) a collective memory; and (6) the personal and solidaristic commitment.…”
Section: Collective Level Of Competenciesmentioning
confidence: 99%
“…From a case study of one complex public-private partnership, Ruuska and Teigland (2009) highlighted four ingredients to ensure project success through collective competence: (1) co-developing a clear project charter; (2) recruiting a project leader with strong knowledge broker skills; (3) conducting joint problem-solving tasks using boundary objects; and (4) ensuring an understanding of the "big picture" through continuous open and balanced communication. For their part, Melkonian and Picq (2010) made use of the insights offered by the very particular world of the French Special Forces, which have been operating successfully for several decades in extreme environments. Based on an in-depth qualitative study of their project-based mode of operations, they detail the six main ingredients of the collective competence that underpins the activities of commando units in mission: (1) the high individual expertise; (2) the combination of different but complementary forms of expertise; (3) the construction of a shared representation, based on common frames of reference and languages; (4) the capacity for collective improvization; (5) a collective memory; and (6) the personal and solidaristic commitment.…”
Section: Collective Level Of Competenciesmentioning
confidence: 99%
“…In a complex business environment, team projects allow companies to earn a major share of their profit (Aubry and Lièvre, 2010;Garel and Lièvre, 2010;Melkonian and Picq, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on individual competence have centered on individuals' skills and abilities and how they assist the team with behaviors and outcomes such as creativity, intrinsic motivation, initiative, and identity reflection (e.g., Boyatzis, 1982;Coatsworth and Conroy, 2009;de Korwin et al, 2002;Partington et al, 2005;Rodolfa et al, 2005;Sansone, 1986;Spencer and Spencer, 1993;Vallerand and Reid, 1984). On the team level, studies have reported the effects of team competence on seizing growth opportunities (Kor, 2003), delegating specific tasks (Zhang et al, 2009), and performance on new products or projects (Haon et al, 2009, Jha andIyer, 2007;Melkonian and Picq, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, the project management literature has highlighted that recruiting highly competent project leaders and project team members does not guarantee success and that such recruitments may sometimes be disappointing (e.g., Green and Compton, 2007;Lampel, 2001;McComb, Müller and Turner, 2010;Jha and Iyer, 2007). Moreover, the project management literature has highlighted that teams that are objectively deemed less competent may sometimes outperform more competent teams (Melkonian and Picq, 2010). Although no foundation exists to argue that competence does not, indeed, contribute to attaining goals, a growing body of research examines how the relationship between competence and goal attainment may be more complex than previously theorized.…”
Section: Introductionmentioning
confidence: 99%